Pharmacogenetic effects of inhaled salbutamol on 10-km time trial performance in competitive male and female cyclists - Koch, S.; MacInnis, M. J.; Rupert, J. L.; Sporer, B.; Koehle, M. (Clinical Journal of Sport Medicine, 2016)
Objective: To determine the effects of single nucleotide polymorphisms (SNPs) in the adrenergic ß2-receptor gene (ADRB2, rs1042713, and rs1042714) and epithelial Na+ channel gene (SCNN1A, rs2228576) on cycling performance after the inhalation of salbutamol.